MODELLING CONFLICT DYNAMICS IN AN ENERGY SUPPLY SYSTEM - Usenik, Janez; Turnšek, Tit (Journal of Energy Technology, 2024)
This paper presents a model of conflict, the precise definition of which is also presented in this paper. The system dynamics paradigm is often used to model the dynamics of social interactions. The basic ideas leading to conflict models in form of difference, i.e. differential equations, and finally to an expanded model with fuzzy logic inference are presented. Tremendous progress in this field has been made by two groups of researchers. Gottman et al., [1], modelled marital interactions and set up a model in the form of differential equations. Coleman in his group, [2], established the model of group interaction in the form of differential equations. There are many types of social interactions; conflict is merely one of them. We define conflict as a destructive, dysfunctional interaction between actors. According to thisview, we developed a conflict model, arising from the model of Coleman et al., first in the form of differential equations and then in the form of a stock-and-flow diagram, according to paradigm of system dynamics. We attempted to keep the results of the model understandable for a broad range of managers and officials at different levels within the energy sector. At the end, a numerical example is given.